Understanding URDF: A Dataset and Analysis - Tola, Daniella; Corke, Peter (IEEE robotics and automation letters, 2024)
The complexity of robot systems is rising which makes it increasingly effective to simulate before deployment. To do this, a model of the robot's kinematics or dynamics is required, and the most commonly used format is the Unified Robot Description Format (URDF). This article presents the first dataset of URDF files with metadata and analysis. The dataset contains 322 URDF files from various industrial and research organizations, and the metadata describes each robot, its type, manufacturer, and the source of the model. The files correspond to 195 unique robot models - the excess URDFs correspond to either multiple definitions across sources, or URDF variants of the same robot. We analyze the files in the dataset and provide information on how they were generated, which mesh file types are most commonly used, and compare models of multiply-defined robots. The purpose of this article is to create foundational knowledge about URDF files, how they are created and used, and generate insight into the current state of the URDF format. Publishing the dataset, analysis, and the scripts and tools used enables others using, researching or developing URDFs to easily access this data and use it in their own work.